Apuntes fenomenológicos sobre el problema del yo y la conciencia en la filosofía de Sartre (2019)
This article is a review of the problem that emerges from the first part of “Transcendence of the Ego” written by Jean-Paul Sartre. The basis of this problem is about the ego possibility of life inside of the conscience. This thinking will reveal the Sartrean thesis about consciousness, which understands consciousness as pure exteriority, that’s means, no metaphysical entity inhabits its interior, as it could be the self, the cogito, the unconscious etc. The impossibility and inconsistency of these metaphysical structures inhabiting the interior of consciousness will be continually argued.